PENGARUH KEMANDIRIAN PRIBADI, BUDAYA ORGANISASI DAN PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH - Nuryanti .; Ramadhan Syahputra; Muhammad Ihsan Hrp; Radhiah .; Elviana Sinaga (Universitas Islam Sumatera Utara, 2021)
The problem of this research is: Do independence, organizational culture, and monitoring an effect on employee work discipline. This study aims to determine the effect of independence, organizational culture, and supervision on employee work discipline. With the Total Sampling technique, the sample in this study was 65 people. Personal independence partially has a positive effect on employee work discipline; Organizational culture partially has a positive effect on employee work discipline; Supervision partially has a positive effect on employee work discipline; Personal independence, organizational culture and supervision simultaneously have a positive and significant effect on employee work discipline.